Post-symptomatic detection of COVID-2019 grade based mediative fuzzy projection. (July 2022) - Sharma, Mukesh Kumar; Dhiman, Nitesh; Mishra, Vishnu Narayan; Mishra, Lakshmi Narayan; Dhaka, Arvind; Koundal, Deepika
HIghlights: The concepts of mediative fuzzy relation as well as mediative fuzzy extension to handle the contradictory, non-contradictory and doubtful information have been developed. The intuitionistic fuzzy projection and its extended concept i.e., mediative fuzzy projection has been defined. The applicability of proposed mediative fuzzy projection in the medical field has been discussed in this work. The impact and credibility of mediative factor in context of prediction work in relation to the proposed model has been shown in this work. Abstract: The concept of fuzzy set, intuitionistic set, and mediative fuzzy set as a generalization of a crisp set have been introduced in many real-life applications. The concept of crisp relation between elements of sets can be extended to fuzzy relations. Extended relations will be considered as relations on fuzzy sets. In this work, we developed the concept of mediative fuzzy relation and meditative fuzzy projection in the context of fuzzy relation and fuzzy projection. We extended the basic operations of fuzzy projection into intuitionistic fuzzy projection and then in the mediative fuzzy projection. We have shown the credibility and impact of mediative index factor involves in the mediative fuzzy projection in context of prediction work in relation to the proposed model. Further, we applied the mediative fuzzy projection in the medical diagnosis in post-COVID-19 patients. The obtained results have also been discussed with their geometrical representation. Graphical abstract: Image, graphical abstract